2003
DOI: 10.1021/bp025789r
|View full text |Cite|
|
Sign up to set email alerts
|

Reverse Micellar Extraction and Precipitation of Lysozyme Using Sodium Di(2-ethylhexyl) Sulfosuccinate

Abstract: Sodium di(2-ethylhexyl) sulfosuccinate, referred to as Aerosol-OT or AOT, was used to remove lysozyme from an aqueous phase via reverse micellar extraction and precipitation method. For both methods, when the surfactant was in excess, a complete removal of lysozyme from the aqueous phase was obtained at the values of pH below the pI of lysozyme. However, for the reverse micellar method, a solubilization limit of lysozyme in the organic phase was observed, and a white precipitate was formed at the aqueous-organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…The results indicated that the complex was unstable in the micellar phase, or in other words, the CB-Span 85 conjugate solubility in the reversed micelles decreased upon the complex formation with the protein. Similar phenomenon was also reported in the extraction of lysozyme with AOT reversed micelles [32,33]. Once getting contacted with a high ionic strength stripper, the complex was Table 1 Total recovery yields (E t ) of lysozyme stripped from different volumes of the organic phase (V o ) with and without hexanol addition (3 vol dissociated gradually and a transparent two-phase system was recovered.…”
Section: Effect Of Hexanol Additionsupporting
confidence: 73%
“…The results indicated that the complex was unstable in the micellar phase, or in other words, the CB-Span 85 conjugate solubility in the reversed micelles decreased upon the complex formation with the protein. Similar phenomenon was also reported in the extraction of lysozyme with AOT reversed micelles [32,33]. Once getting contacted with a high ionic strength stripper, the complex was Table 1 Total recovery yields (E t ) of lysozyme stripped from different volumes of the organic phase (V o ) with and without hexanol addition (3 vol dissociated gradually and a transparent two-phase system was recovered.…”
Section: Effect Of Hexanol Additionsupporting
confidence: 73%
“…On the other hand, these techniques are not easily scalable. Liquid-liquid extraction of proteins using reverse micellar phase was proposed as an alternative method [5]. Normally reverse micellar extraction involves the use of volatile organic solvents such as isooctane [6].…”
Section: Introductionmentioning
confidence: 99%
“…Low interfacial tension, ease of scale-up, and potential for continuous operation are some of the advantages of reverse micellar extraction (RME) (2,3). Several reports on the application of RME for separation and purification of biomolecules are available for model systems (4)(5)(6)(7)(8). In recent years, a few studies on RME of biomolecules from natural=real systems have been reported (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%